1991
DOI: 10.1128/jvi.65.10.5485-5490.1991
|View full text |Cite
|
Sign up to set email alerts
|

Identification and mapping of neutralizing epitopes of human parvovirus B19 by using human antibodies

Abstract: We identified and mapped the regions responsible for neutralization in the human parvovirus B19 structural protein by using region-specific human antibodies derived from seropositive blood donors. The region-specific antibodies were purified by using affinity columns coupled with synthetic peptides of the hydrophilic regions including the s-turn structure deduced by the predicted secondary structure of VP2. Fifteen highly specific antibodies against the synthetic peptides were obtained. Ten of them were able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 32 publications
2
24
0
1
Order By: Relevance
“…As observed for the HBoV1-specific MAbs, the 2-/5-fold wall and 3-fold protrusions are hot spots for the majority of the antigenic footprints of other parvoviruses, including the AAVs, Aleutian mink disease virus (AMDV), B19, and canine parvovirus (CPV), and utilize residues within VR-I, VR-III, VR-IV, VR-V, VR-VI, and VR-VIII ( Fig. 8) (62)(63)(64)(65)(66)(67)(68)(69)(70). For example, residues within VR-I and VR-III are important for serotype-specific antibody interactions for the AAVs, including the AAV1-ADK1a, AAV2-A20, AAV2-D3, AAV5-ADK5a, and AAV5-3C5 antibody interactions.…”
Section: Discussionmentioning
confidence: 99%
“…As observed for the HBoV1-specific MAbs, the 2-/5-fold wall and 3-fold protrusions are hot spots for the majority of the antigenic footprints of other parvoviruses, including the AAVs, Aleutian mink disease virus (AMDV), B19, and canine parvovirus (CPV), and utilize residues within VR-I, VR-III, VR-IV, VR-V, VR-VI, and VR-VIII ( Fig. 8) (62)(63)(64)(65)(66)(67)(68)(69)(70). For example, residues within VR-I and VR-III are important for serotype-specific antibody interactions for the AAVs, including the AAV1-ADK1a, AAV2-A20, AAV2-D3, AAV5-ADK5a, and AAV5-3C5 antibody interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In most individuals infection results in seroconversion with the resulting neutralising IgG antibodies affording life-long protection from re-infection [4]. Such antibodies are directed at a variety of neutralising epitopes on VP-1 and VP-2, and current vaccine developments are based on this knowledge [5][6][7]. The non-structural proteins have been shown to be directly cytotoxic, and may explain the cytopathic effects of B19 on cell types non-permissive for replication [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…VP2 protein is the major capsid protein and has epitopes recognized by a neutralization antibody. Sato et al [1991] identified the neutralizing epitopes using a CFU-e assay with affinity column purified human antibodies; they showed that the neutralizing epitopes were distributed in the region from amino acid 253 in the amino-terminal portion of VP2, with peak neutralization activity in amino acids 325-345. A mutation of amino acid 310 was also found in this region, but it was outside of the peak.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been established to detect the B19 virion or its genome, including double immunodiffusion [Cossart et al, 1975], countercurrent immunoelectrophoresis [Cossart et al, 1975], enzyme immunoassay [Sato et al, 1991], radioimmunoassay , dot blot hybridization [Anderson et al, 1985;Clewly, 1985], and PCR [Clewly, 1989;Koch and Adler, 1990]. These methods, however, are not applicable for mass donor screening at blood centers.…”
Section: Introductionmentioning
confidence: 99%